Immunosuppressant Prograf (R) (Tacrolimus) Induces Histopathological Disorders in the Peritubular Tissue of Rat Testes - Caneguim, Breno H.; Cerri, Paulo Sérgio [UNESP]; Spolidório, Luis Carlos [UNESP]; Miraglia, Sandra M.; Cerri, Estela Sasso [UNESP] (Karger, 2011)
Treatment with tacrolimus (FK-506) has been shown to induce a significant decrease in the number of spermatocytes, spermatids, and Sertoli cells. Regarding the importance of the peritubular tissue for the maintenance of Sertoli cells, the integrity of the cellular and extracellular components of the peritubular tissue was evaluated in adult rats that were treated with 1 mg/kg/day of FK-506 for 30 and 60 days. Testicular sections were used for a quantitative analysis of the peritubular cells (PCs) and were submitted to the PAS method. Paraffin sections were submitted to the TUNEL method and to immunohistochemistry for the detection of caspase-3. Several testicular fragments were analyzed under a transmission electron microscope (TEM). A weak PAS reaction was noted in the peritubular tissue of the tacrolimus-treated animals. Next to the damaged peritubular tissue, the Sertoli cell nuclei were absent or dislocated from the basement membrane. In the treated animals, the number of PCs decreased significantly compared to the control animals, and these cells showed apoptotic features, were TUNEL positive, and were caspase-3 immunolabeled. Using the TEM, apoptosis was confirmed in myoid cells; moreover, the thickness and undulation of the basal laminae and an enlargement of the collagen I layer adjacent to the myoid cells was observed. Long-term treatment with the immunosuppressor induced peritubular myoid cell death by apoptosis and disarrangement of the peritubular extracellular layers. Future studies are necessary to confirm whether the structural alterations in the seminiferous epithelium are related to the effect of FK-506 on peritubular tissue. Copyright (C) 2011 S. Karger AG, Basel
Keywords: FK-506; Myoid cell death; Peritubular tissue; Sertoli cell; Ultrastructure